The effects of three different low-volume aerobic training protocols on cardiometabolic parameters of type 2 diabetes patients: A randomized clinical trial - Paulo Gentil; Paulo Gentil; Paulo Gentil; Lucas Raphael Bento e Silva; Lucas Raphael Bento e Silva; Lucas Raphael Bento e Silva; Daniela Espíndola Antunes; Luciana Barbosa Carneiro; Claudio Andre Barbosa de Lira; Claudio Andre Barbosa de Lira; Gislene Batista; Jordana Campos Martins de Oliveira; et al. (Frontiers in Endocrinology, 2023)
ObjectiveTo compare the effects of different aerobic training protocols on cardiometabolic variables in patients with type 2 diabetes mellitus (T2DM).MethodsThis study was a parallel clinical trial. Fifty-two men and women with T2DM (>40 years) were randomly allocated into three groups, and 44 (22 males/22 females) were included in the final analysis. Exercise intensity was based on the speed corresponding to the maximum oxygen consumption (vV˙O2max). Moderate intensity continuous training (MICT) involved 14 minutes at 70% of vV˙O2max; short interval high-intensity interval training (S-HIIT) consisted of 20 bouts of 30 seconds at 100% of V˙O2max with 30 seconds passive recovery; long interval high-intensity training (L-HIIT) consisted of 5 bouts of 2 minutes at 100% of vV˙O2max with 2 minutes passive recovery. Training protocols were performed on a motorized treadmill two times per week for eight weeks. Glycated hemoglobin (Hb1Ac), total cholesterol, triglycerides, resting systolic blood pressure (SBP), resting diastolic blood pressure (DBP), resting heart rate (resting HR) and maximum oxygen consumption (V˙O2max) were measured before and after the exercise intervention. The study was registered on the Brazilian clinical trial records (ID: RBR45 4RJGC3).ResultsThere was a significant difference between groups for changes on V˙O2max. Greater increases on V˙O2max were achieved for L-HIIT (p = 0.04) and S-HIIT (p = 0.01) in comparison to MICT group, with no significant difference between L-HIIT and S-HIIT (p = 0.9). Regarding comparison within groups, there were significant reductions on HbA1c and triglycerides levels only for L-HIIT (p< 0.05). V˙O2max significantly increased for both L-HIIT (MD = 3.2 ± 1.7 ml/kg/min, p< 0.001) and S-HIIT (MD = 3.4 ± 1.7, p< 0.001). There was a significant reduction on resting SBP for L-HIIT group (MD = -12.07 ± 15.3 mmHg, p< 0.01), but not for S-HIIT and MICT. There were no significant changes from pre- to post-training on fasting glycemia, total cholesterol, HDL, LDL, resting HR and resting DBP for any group (p > 0.05).ConclusionLow-volume HIIT promoted greater improvements in cardiorespiratory capacity in comparison with low-volume MICT, independent of the protocols used. There were no other differences between groups. All protocols improved at least one of the variables analyzed; however, the most evident benefits were after the high-intensity protocols, especially L-HIIT.